PENGARUH PENERIMAAN PAJAK REKLAME, PAJAK RESTORAN DAN PAJAK HOTEL TERHADAP PENDAPATAN ASLI DAERAH (PAD) KOTA SURAKARTA TAHUN 2020-2024 - Diva Tiara Saraswati; Desy Nur Pratiwi; Rukmini Rukmini (CV. Denasya Smart Publisher, 2026)
This study aims to examine the effect of advertisement tax revenue, restaurant tax revenue, and hotel tax revenue on Regional Original Revenue (PAD) of Surakarta City for the period 2020–2024. This research uses secondary data collected through documentation and literature review methods. The analytical techniques employed in this study are multiple linear regression analysis and the coefficient of determination (Adjusted R²) using SPSS version 25. The population in this study consists of monthly realization reports of advertisement tax, restaurant tax, hotel tax, and Regional Original Revenue (PAD) of Surakarta City for 2020–2024 obtained from the Regional Revenue Agency (Bapenda) of Surakarta City, totaling 60 observations, with saturated sampling used as the sampling technique. The results show that advertisement tax revenue has a positive and significant effect on PAD, restaurant tax revenue also has a positive and significant effect on PAD, while hotel tax revenue does not have a significant effect on PAD. Furthermore, the Adjusted R² value of 94.5% indicates that 94.5% of the variation in PAD can be explained by advertisement tax, restaurant tax, and hotel tax revenues, while the remaining 5.5% is influenced by other variables not included in this study.